The Influence of Motivation and Work Discipline in Efforts to Increase Employee Work Productivity with Work Quality as an Intervening Variable at the Patumbak District Office - Ananda Armaya; Muhammad Toyib Daulay (International Journal of Society and Law, 2024)
The research analysis aims to determine the influence of work motivation and discipline in efforts to increase employee work productivity with work quality as an intervening variable at the Patumbak District Office. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses intervening regression analysis. The sample in this study was 34 respondents. Primary data collection uses a questionnaire. The results of the research show that motivation has a positive and significant effect on the quality of work at the Patumbak District Office. Work discipline does not have a significant effect on the quality of work at the Patumbak District Office. Motivation does not have a significant effect on employee productivity at the Patumbak District Office. Work discipline influences employee productivity at the Patumbak District Office. Work quality does not have a significant effect on the productivity of Patumbak District Office employees. Indirectly, motivation through quality does not have a significant effect on the work productivity of the Patumbak District Office. Indirectly, motivation through quality does not have a significant effect on the work productivity of the Patumbak District Office.